Planning valued landscapes as potential tourism attractions for national development: the case of Yoruba, Nigeria - Moses, Adedokun Olutoyin (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Researches in environmental planning in developing countries are largely dominated by provision of infrastructures such as housing, transportation, sewage disposal etc. Very few works have examined an important aspect of planning, that is, landscape planning. This work, therefore, examines the importance of landscape planning not only as an avenue for preservation of identity, but as a source of tourist attraction and revenue generation for the country. This is because tourism all over the world is an instrument of socio-economic development, it also promotes peace and stability in developing countries by providing jobs, generating income, diversifying the economy, protecting the environment and promoting cross-cultural awareness.